2013
DOI: 10.1080/21580103.2013.846875
|View full text |Cite
|
Sign up to set email alerts
|

REDD+ as an international cooperation strategy under the global climate change regime

Abstract: Under the global climate negotiations, a REDDþ (Reducing Emissions from Deforestation and Forest Degradation, conservation of forest carbon stocks; sustainable management of forests, and enhancement of forest carbon stocks) regime is established by multi-stakeholders such as transnational organizations, states, and non-governmental organizations (NGOs). However, several developed countries have strategically exerted their leadership in forming and implementing a REDDþ regime in the international community. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Previous studies provided important guidelines for the architecture of the emerging international REDD+ regime. Examples are the works of Corbera, Estrada, and Brown (2010), Corbera and Schroeder (2011), Gupta (2012) Park, Choi, and Youn (2013), Phelps, Webb, and Agrawal (2010), and Somorin et al (2012). Most of these studies have a political economics approach.…”
Section: Gap In the Literaturementioning
confidence: 99%
“…Previous studies provided important guidelines for the architecture of the emerging international REDD+ regime. Examples are the works of Corbera, Estrada, and Brown (2010), Corbera and Schroeder (2011), Gupta (2012) Park, Choi, and Youn (2013), Phelps, Webb, and Agrawal (2010), and Somorin et al (2012). Most of these studies have a political economics approach.…”
Section: Gap In the Literaturementioning
confidence: 99%
“…Previous studies provided important guidelines for the architecture of the emerging international REDD+ regime. Examples are the works of Corbera, Estrada, and Brown (2010), Corbera and Schroeder (2011), Gupta (2012), Hajek, Ventresca, Scriven, and Castro (2011), Kanowski, McDermott, and Cashore (2011), Karsenty (2008), Levin, McDermott, and Cashore (2008), Park, Choi, and Youn (2013), Phelps, Webb, and Agrawal (2010), and Somorin et al (2012). Most of these studies have a political economics approach.…”
Section: Systematic Analysis Of Redd+ Studiesmentioning
confidence: 99%
“…Yet these issues remain unresolved. For example, Schmitt et al (2009); Park et al (2013); Keenan et al (2015) and FAO (2016) asserted that there was a 3% net decrease in global forest area between 1990 and 2015, from 4128 M ha to 3999 M ha. In addition, FAO (2018, p.xi) reported that forest cover decreased from 31.6% to 30.6% of global land area between 1990 and 2015, while UN (2015) estimated that at least 5.1 million hectares of forest had been lost by 2010.…”
Section: The Relationship Between Forest Resources Rural Livelihoodsmentioning
confidence: 99%
“…Consequently, significant global resolutions have called for attention to climate change to reduce emissions from deforestation and forest degradation and manage forests sustainably. Examples include; 1) UNFCCC (UN 1992;Park et al 2013); 2) the adoption of the Paris Agreement (UN 2015a;Bretschger et al 2018;Nieto et al 2018 Under SDG15, the State Parties agreed to protect, restore and promote sustainable use of terrestrial ecosystems, sustainably manage forests, combat desertification, and halt and reverse land degradation and halt biodiversity loss (UN 2015c). This requires them to implement policies and national plans of action, build capacity and arrange their national institutions accordingly.…”
Section: The Relationship Between Forest Resources Rural Livelihoodsmentioning
confidence: 99%